Pediatric Multisystem Inflammatory Syndrome (MIS-C) temporally associated with covid-19: a cross-sectional study (Revista Contexto & Saúde, 2025)
Objective: To analyze the occurrence of cases of MIS-C, temporally associated with covid-19, in the State of Ceará. Method: This is a cross-sectional study of a secondary database containing 82 cases of children and adolescents notified with MIS-C associated with covid-19, in the State of Ceará, from 2020 to 2021. RStudio® was used to calculate the data. Results: The following were more severe: adolescents aged 10 to 14 years, with hospitalizations of more than 10 days, mean of 36 days between hospitalization and notification, with ICU admission, detection for SARS-CoV-2 by RT-PCR, imaging tests with infiltrate, ascites, and myocardial dysfunction; treatment with corticosteroids, outcome for death, hospital discharge without sequelae and closure according to laboratory criteria. Conclusion: The findings of this study support early diagnosis, allowing the reduction of negative outcomes and a better prognosis.
Keywords: COVID-19; Systemic Inflammatory Response Syndrome; Epidemiology; Cross-sectional studies